Monitoring and Evaluation of Agricultural Policy Indicators - Roehlano M. Briones; Cristina C. David; Arlene B. Inocencio; Ponciano Jr. S. Intal; Maria Piedad S. Geron; Marife M. Ballesteros (Philippine Institute for Development Studies (PIDS), 2012)
This study proposes a set of indicators for monitoring and evaluation of agricultural policy, patterned after the support estimates of the Organization for Economic Cooperation and Development (OECD). The main indicators are: producer support (incorporating indirect market support, and direct input support through irrigation, credit, and land transfer); general services support; and public expenditures for agriculture. The study finds that these indicators are viable measures of public support and may be consistently updated over time. Past trends in policy indicators suggest that price policy played the biggest role in agricultural support. Low to negative support to agriculture up to the late 1980s was due largely to indirect taxation of agriculture. From the 1990s onward though the protection structure swung in favor of agriculture resulting in expanding producer support, further enhanced by increasing budgetary outlays for agriculture, mostly toward provision of private goods (such as fertilizer subsidies). These patterns suggest resource misallocation, which may be remedied by rationalizing price policy as well as budgetary allocation from agricultural support services of DA (and land acquisition by DAR), toward provision of public goods such as R&D, extension, regulation, and participatory irrigation investments.
Keywords: 330; agricultural support; price policy; public goods